Ancient Egypt - Oachs, Emily Rose (Ancient civilizations (Bellwether Media), 2020)
Simple text, photographs, and illustrations introduce learning readers to some unique features of ancient Egypt, including their culture, major cities, and their religion. Includes a glossary.